Poets & Prophets of the Resistance. Intellectuals & the Origins of El Salvador’s Civil War, by Joaquín M. Chávez - Luis (Realidad: Revista de Ciencias Sociales y Humanidades, 2023)
No abstract available. Realidad: Revista de Ciencias Sociales y Humanidades No. 162, 2023: 85-86.